k-Servers with a Smile: Online Algorithms via Projections - Buchbinder, Niv; Gupta, Anupam; Molinaro, Marco; Naor, J. (SODA, 2019)
We consider the k-server problem on trees and HSTs. We give an algorithms based on %the convex-programming primitive of Bregman projections. This algorithm has a competitive ratios that match some of the recent results given by Bubeck et al. (STOC 2018), whose algorithm was based on mirror-descent-based continuous dynamics prescribed via a differential inclusion.